Successful community-based tourism approaches for rural destinations: The Asia Pacific experience. (9th November 2015) - Nair, Vikneswaran; Hamzah, Amran
Abstract : Purpose: – The purpose of this paper is to provide a better understanding of the long-term viability of community-based tourism (CBT) as a development tool in rural tourism, and how the best practice from the Asia Pacific region can be used to strategize the nine-stage plan to develop and sustain it in the long term. Design/methodology/approach: – This paper is formulated using a case study approach based on the lessons learned and the best practices in ten member economies of the Asia Pacific Economic Cooperation (APEC) Forum, namely, Australia, Canada, China, Chinese Taipei, Indonesia, Korea, Malaysia, New Zealand, the Philippines and Vietnam. Findings: – Based on the analyses of the ten case studies, the paper recommends nine steps for developing and sustaining CBT. These nine steps are divided into two sections – developing CBT and sustaining CBT. The first four steps relate to starting and developing CBT initiatives, which are useful for projects and sites that are embarking on CBT. The subsequent five steps are meant to address the sustainability of CBT projects, which are more appropriate for mature CBT projects that are gradually moving up the value chain. The nine steps are presented in detail and supported by the models developed from the case studies. For each step, a list of actions is recommended to guide the development of CBT. Research limitations/implications: – This paper is limited by the ten case studies selected by the researcher. The conditions for these selected case studies may not be identical in other locations, and thus, the proposed nine-step framework can be used only as a guide. Each step outlined may vary from one nation to another. Originality/value: – The main output of this paper is designed to provide guidance for tourism/rural planners, non-government organizations (NGOs), industry players and CBT organizations in deciding whether tourism could work for a particular community and if it is feasible to be sustained over the long term.